Does the development of intra-industrial trade leading to environmental degradation in the EU-28? - Afef Souguir (Cogent Social Sciences)
In the context of globalization, the growing importance of international relations and the emergence of environmental issues have inspired a new sense of political and economic interaction. Therefore, the pattern of trade has changed, leading to global trade reforms. Moreover, trade in differentiated goods is valued and encouraged in EU member states, where intra‑industry trade is increasingly replacing inter‑industry. Thus, we will assess, in this study, the relationship between the intensity of intra‑industry trade in manufacturing, renewable energy (RE), per capita income (GDPPC), the size of the industrial sector in the total economy (INDUSTRY) and carbon dioxide (CO2) emissions from 2002 to 2018 for the EU‑28 countries. The estimation method used in this research work is the dynamic panel Generalized Moment Method (GMM‑System Two‑Step) advocated by Arellano & Bover (1995). The empirical study showed that renewable energy trade intensity and per capita income contribute to environmental improvement. In addition, the size of the industrial sector in the total economy has a positive impact on CO2 emissions.